Plant Species Diversity and Degree of Homogeneity after the 2010 Eruption of Mount Merapi, Indonesia - Whisnu Febry Afrianto; Agus Hikmat; Didik Widyatmoko (Biosaintifika: Journal of Biology & Biology Education, 2020)
The eruption in 2010 of Merapi Mount changed the diversity of plant species. The objective of this research was to investigate the diversity of plant species on Mount Merapi National Park (MMNP). The sampling area was divided into three different levels of damage (heavy, medium, and mirror). The research was conducted by using line-transect and quadrat method. Â We were conducted using line-transect and quadrat method. The research showed that Acacia decurrens has the highest Important Value Index (IVI) at the heavy damage area of Cangkringan Resort (CR) and Kemalang Resort (KR) as well as in mirror damage area of Selo Resort (SR). The most important species at medium damage area of Dukun Resort (DR) were Albizia lopantha and Pinus merkusii. The pioneer species at Non-Cover Area (NCA) among others were Trema cannabina, Pityrogramma calomelanos, Imperata cylindrical, Buddleja asiatica, Anaphalis javanica. Eupatorium riparium were the most important species of herb in all four locations based on SIMPER, but it was not dominant in NCA. The homogeneity of plant in Cangkringan Resort and Selo Resort (C D E) were normally distributed, whereas NCA, DR, and KR (E â‰¥ D) were homogeneous. Analysis of non-metric multidimensional scaling and value of ANOSIM (RANOSIM =0.69; p = 0.0001) demonstrated that all site locations have significance differences. This research was not only focusing on survey of vegetation diversity, but also frequency class distribution. Through this study of frequency of species provides a database for conservation biodiversity and restoration program.